Inspection at summerhill - Keeble-Ramsay, Diane (Revista Hipótese, 2017)
This paper considers issues surrounding the 1999 OFSTED inspection of Summerhill school (in Suffolk) which led to a Notice of Closure, and subsequent successful appeal on the grounds of inappropriate judgements made by OFSTED inspectors. It is useful to note that Summerhill School has existed in the independent sector offering ‘progressive education’ since the 1920s. However, following a 1990s inspection from OFSTED, its existence was threatened in terms of its freedom in future continuing to offer an independent UK-based fully ‘democratic’ schooling (despite the fact that parents pay for their children to attend Summerhill outside any UK state offering). This paper identifies problems for organisations subject to inspection which do not conform to the formal organisation model.
Keywords: Summerhill; School Effectiveness; Independent School Inspection